Pelaksanaan Perlindungan Hukum bagi Penyandang Disabilitas dalam Mendapatkan Pelayanan Publik di Kabupaten Tabanan - I Putu Sumardika; I Wayan Wesna Astara; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2021)
For people with disabilities, mobility is important, especially in obtaining public services through the expansion of access to avoid discrimination because of its integral role in participating in social activities. This paper aims to discuss the forms of legal protection and its implementation for persons with disabilities in the Tabanan Regency. Then, it is also intended to explore the conditions of legal guarantee provisions for disabilities related to access to public services. This study is classified as an empirical legal study that uses various methodological approaches, including sociology of law; conceptual, and legislation. Meanwhile, the study data collected were obtained through literature studies, interviews, and observations. In the end, it was discovered that there were adequate provisions regarding regulations that discussed legal protection for persons with disabilities whose rights were targeted in the formation of related laws. Meanwhile, several obstacles faced in the implementation of legal protection related to access to public services, among others, limited awareness of parents with children with disabilities, budget funds, and the lack of professionalism of human resources. Finally, the regulations stipulated on the protection of the human rights of persons with disabilities must be made into a Tabanan district regulation.